Candida albicans and Candida dubliniensis: comparison of biofilm formation in terms of biomass and activity - Henriques, Mariana (2006)
Candida albicans and C. dubliniensis are two species responsible for oral candidiasis, especially in immunocompromised patients. Microbial infection is preceded by adherence and biofilm formation. Biofilm formation represents the most common form of C. albicans in the oral cavity and is considered to be one of the most important virulence factors. In this study, the biofilm formation ability of C. dubliniensis was compared with that of C. albicans in terms of biomass (quantified using crystal violet) and activity (assessed by formazan salts formation). Both species formed heterogeneous biofilms; however, species and strain variations were seen in the quantification of biomass and activity. There was no correlation between pseudohyphae formation and biofilm formation capability.